2006
DOI: 10.1017/s0950268806007011
|View full text |Cite
|
Sign up to set email alerts
|

Discernment between deliberate and natural infectious disease outbreaks

Abstract: Public health authorities should be vigilant to the potential for outbreaks deliberately caused by biological agents (bioterrorism). Such events require a rapid response and incorporation of non-traditional partners for disease investigation and outbreak control. The astute application of infectious disease epidemiological principles can promote an enhanced index of suspicion for such events. We discuss epidemiological indicators that should be considered during outbreak investigations, and also examine their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 80 publications
(74 reference statements)
0
51
0
3
Order By: Relevance
“…In addition to accidental or unintentional environmental exposure, the current political climate makes the malicious misuse of BoNTs, through acts of terrorism, a serious possibility. 10 There are 7 biochemically distinct BoNT serotypes (designated A-G). BoNT holotoxins are composed of 2 subunits: the heavy chain (HC), which mediates entry into neurons via receptor-mediated endocytosis, and a Zn-metalloprotease component referred to as the light chain (LC).…”
mentioning
confidence: 99%
“…In addition to accidental or unintentional environmental exposure, the current political climate makes the malicious misuse of BoNTs, through acts of terrorism, a serious possibility. 10 There are 7 biochemically distinct BoNT serotypes (designated A-G). BoNT holotoxins are composed of 2 subunits: the heavy chain (HC), which mediates entry into neurons via receptor-mediated endocytosis, and a Zn-metalloprotease component referred to as the light chain (LC).…”
mentioning
confidence: 99%
“…Delayed diagnosis can cause a fatal outcome. Mild or unapparent forms of tularemia with sero-conversion seem to be more common than previously thought even in low-prevalence areas according to a recent sero-epidemiological study in Germany [45,46].…”
Section: Humansmentioning
confidence: 83%
“…Years later, a joint team formed by Soviet and Western physicians and scientists re‐examined the case and showed that the outbreak was caused by inhalation of anthrax spores and that the point of origin was Sverdlovsk‐19, a military research facility, where a clogged air filter was removed and not replaced. It is known that the former Soviet Union had a massive bioweapons program , pointing out for the possibility of victims being exposed to different B. anthracis strains due to aerosol release of anthrax formulation from the military research facility .…”
Section: Zoonotic Outbreaks Not Related To Warsmentioning
confidence: 99%